1997
DOI: 10.1128/jb.179.8.2534-2539.1997
|View full text |Cite
|
Sign up to set email alerts
|

The pst operon of Bacillus subtilis has a phosphate-regulated promoter and is involved in phosphate transport but not in regulation of the pho regulon

Abstract: Genes from Bacillus subtilis predicted to encode a phosphate-specific transport (Pst) system were shown by mutation to affect high-affinity P i uptake but not arsenate resistance or phosphate (Pho) regulation. The transcription start of the promoter upstream of the pstS gene was defined by primer extension. The promoter contains structural features analogous to the Escherichia coli pst promoter but not sequence similarity. Expression from this promoter was induced >5,000-fold upon phosphate starvation and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
193
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(199 citation statements)
references
References 40 publications
4
193
1
1
Order By: Relevance
“…Using a combination of reporter gene and DNA array technology, we have shown that pit expression is independent of P i concentration and PhoPR (N. E. E. Allenby, C. R. Harwood & Z. Prágai, unpublished). In contrast, the pst operon is induced specifically in response to P i starvation in a PhoPdependent manner (Qi et al, 1997). The products of this operon form the main transporter of phosphate at low P i concentrations (<0?1 mM) and pst mutants exhibit an approximately sevenfold reduction in P i uptake under these conditions (Prágai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a combination of reporter gene and DNA array technology, we have shown that pit expression is independent of P i concentration and PhoPR (N. E. E. Allenby, C. R. Harwood & Z. Prágai, unpublished). In contrast, the pst operon is induced specifically in response to P i starvation in a PhoPdependent manner (Qi et al, 1997). The products of this operon form the main transporter of phosphate at low P i concentrations (<0?1 mM) and pst mutants exhibit an approximately sevenfold reduction in P i uptake under these conditions (Prágai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The pst operon is transcribed from a sigma A-type promoter located immediately upstream of pstS (Qi et al, 1997). Recently, the operon has been shown to be induced during alkali stress (Atalla & Schumann, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The cell also secretes multiple alkaline phosphatases (APases) Hulett, 1993;1995;1996), alkaline phosphodiesterases (Le Hegarat and Anagnostopoulos, 1973;Yamane and Maruo, 1978a,b;Eder et al, 1996) and other hydrolytic enzymes (Kusser and Fiedler, 1982;1983) to recycle the available phosphorus from teichoic acid (Grant, 1979). The inorganic phosphate produced in this process is then transferred into the cell by an efficient high-affinity phosphate transport system (Eymann et al, 1996;Qi et al, 1997). Some of the genes that are involved in this process, the Pho regulon genes, have been cloned, and their promoter activities have been found to be regulated by two regulatory genes, phoP and phoR, under phosphate starvation conditions Hulett et al, 1990;1994a,b;Chesnut et al, 1991;Eder et al, 1996;Qi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic phosphate produced in this process is then transferred into the cell by an efficient high-affinity phosphate transport system (Eymann et al, 1996;Qi et al, 1997). Some of the genes that are involved in this process, the Pho regulon genes, have been cloned, and their promoter activities have been found to be regulated by two regulatory genes, phoP and phoR, under phosphate starvation conditions Hulett et al, 1990;1994a,b;Chesnut et al, 1991;Eder et al, 1996;Qi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This might be the case if polyphosphate acts as an alarmone signal for activation of the Lon protease rather than as a phosphate storage molecule in M. xanthus, as suggested by Zhang et al (24). In B. subtilis pstSCAB promoter activity is induced ϳ5,000-fold upon P limitation, from ϳ0 to ϳ4,500 U of LacZ (18). In contrast, P limitation in M. xanthus increases the pstSCAB promoter activity from ϳ150 to ϳ650 U of LacZ (Fig.…”
Section: Discussionmentioning
confidence: 93%